Reflexões na formação em pedagogia nos cursos EAD : uma análise histórico-crítica - Sartori, Andressa Pereira Silva (2023)
In the light of Historical-Critical Pedagogy, this research aims to analyze the teacher education in Pedagogy courses in the context of Distance Education in Brazil. For this purpose, the specific objectives were: to understand the historical (de)valuation of teacher education; to investigate the interests of capital in education and its "minimalist" formation strategy enabled by Distance Education; to analyze the implications of teacher education in the Distance Education mode for the working class. The reason for this research stems from the observation that among the distance undergraduate courses in public and private institutions, Pedagogy stands out as the largest one in terms of enrollments, which leads to an analysis of how teacher education has been characterized in Pedagogy courses in the context of Distance Education in Brazil. To address this question, the research followed a methodological path that was grounded in the qualitative approach. Additionally, with the aim of achieving the objectives outlined in this study, a Bibliographic and Documentary Research was undertaken. The former sought to engage with the Historical-Critical Pedagogy as a collective construction of a revolutionary pedagogical theory, the interests of which are critically aligned with the working class. The latter was conducted to provide a more comprehensive understanding of the context of Distance Education teacher training in Brazil. The Documentary Research produced data indicating that the implications of teacher formation in the Distance Education mode for the working class directly undermine the struggle for human emancipation, perpetuating the relationship of exploitation of one human being by another, as well as the existence and maintenance of social classes. This scenario highlights a tangle of factors that point to an exclusive inclusion taking on a new form of structural duality, aiming at the new relationships between education and labor mediated by the process of commodification of education.